The Transformation of Interpersonal Relationships through Social Media in the Digital Age - Djo Day, Yulyanti; Raga, Fransiskus; Leto, Yohanes (Journal Social Humanity Perspective, 2023)
The given qualitative research will discuss the changing nature of the social communication in the digital context, with the emphasis on the implication of the social-media devices on managing interpersonal relationships. With the increasing role of digital environment in mediating between people, queries are raised about the quality, genuineness, and emotional relevance of this communication. One of the highest qualities of the research was in-depth interviews with a diverse sample; it enabled four interconnected themes to be discussed: intensified connectivity in contrast to the superficial interactions, reduced face-to-face communication, an increase in online debates and lack of communication, and impacts of social comparison on self-esteem. Findings show that although social media makes communication quick and convenient, in many cases it provides interactions that are performative and affectively remote. The interviewees have noted that they experienced a loss in face-to-face communication and replaced quality conversations with short and unemotional online messages. Online feeding grounds were also found vulnerable to tension which more often than not happened due to a lack of non-verbal communication as well as to the high cost of mismatched meaning. Besides, long-term contact with curated content in cyberspace was said to deteriorate psychological well-being and the self-perception of people using it. The research provides an empirical contribution, which helps to understand the strategies that people follow to manage these changes in communication and the necessity of digital literacy and emotional awareness in order to develop more profitable and beneficial social relationships in the digital environments that exist today.